The Effect of Substrate Temperature on the Structural Properties of Spray Pyrolysed Lead Sulphide (PbS) Thin Films - Faraj, Mohammad G.; Omar, Halo D. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2014)
Lead sulphide (PbS) films were prepared by the chemical spray pyrolysis technique using a solution of Lead nitrate and thiourea. PbS films were deposited (prepared) on glass substrate at varied temperature (250-350 oC). Effects of substrate temperature on the structural characteristics of the films were studied. The X-ray diffraction patterns’ results reveal that the all of PbS films have a face centered cubic structure. The X-ray diffraction study showed that irrespective of substrate temperature all the films exhibits a preferred orientation along the (200) plane. The degree of preferred orientation increased with the substrate temperature. It was observed that the increase of the substrate temperature increase the diffraction peak intensity of (200) plane which resulted in increase in grain size and good crystallinity of the films.